Electrosynthesis And Electroanalytical Studies Of The Selected Dihydroxybenzene Compounds At Carbon And Poly (4–Vinylpyridine) Based Nanocomposite Electrodes - Hanieh, Ghadimi (2013)
This study has utilized various carbon based electrodes viz. glassy carbon, composite graphite, carbon nanotube and graphene as substrate electrodes. Composite graphite rods were utilised in electro-organic syntheses involving catechol (CT) in the presence of thiosemicarbazide (TSC) at pH 5.3. The oxidation mechanism of which was then suggested. The electro-generated o-quinone had a 1, 4-addition reaction with the TSC, such that an increase in current could be attributed to the re-oxidation of the thiol-catechol adduct and be used for quantification of the thiol. The glassy carbon electrode modified with a poly (4–vinylpyridine) (P4VP) and in combination with multiwalled carbon nanotubes (P4VP/MWCNT–GCE) and also with graphene sheets (P4VP/GR–GCE) using drop–casting method were investigated. The combined effect of P4VP and MWCNT on the electro-oxidation of diphenols and paracetamol (PCT), aspirin (ASA) and caffeine in the sulphate buffer (pH 2.5) and phosphate buffer (pH 7) solutions were observed. The smaller peak separation (ΔEp) for the oxidation of hydroquinone (HQ) and CT indicates that the reversibility of the electrode process was enhanced. The simultaneous determination of both compounds was also possible.